The Role of Sanctions In The Age of Social Media: Tax Compliance: Case Study of Student of the Faculty of Economics, Mercu Buana University - Nun Syaroni; Lucky Nugroho (School of Accountancy, University of Agung Podomoro, 2026)
This study aims to analyze the influence of tax knowledge, fiscal service quality, tax sanctions, and tax information on social media on the tax compliance of Generation Z of employee class students of Mercu Buana University (UMB) Faculty of Economics & Business. This quantitative research used a five-scale Likert questionnaire to 100 Gen Z respondents who worked and were regular students of 2 UMB. Data were processed by multiple linear regression using SPSS 26. The results of the study show that tax sanctions have a positive and significant effect on tax compliance, while tax knowledge, fiscal service quality, and information on social media have a positive/negative but insignificant effect. These findings indicate that for Gen Z of the working class, tax compliance is driven more by the perception of sanction risk than by the aspect of knowledge and quality of service. This research provides implications for tax authorities and universities to design educational strategies that are not only informative, but also touch on psychological and behavioral factors.